REFORMASI PELAYANAN PENYANDARAN KAPAL DAN PENGURUSAN DOKUMENTASI BARANG DI KANTOR ADMINISTRASI PELABUHAN TANJUNG PERAK SURABAYA - Puspito, Ery (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Transportation services by sea transportation modes required a lot of things that support theimplementation of transportation activities. Another contributing factor between the shipfor transporting cargo or goods that will be used as a production tool for industrialcompanies. On the ship berthing activities and documentation of ship operations, arerequired to complete the insert and dismantling with time as soon as possible. The purposeof this study is to analyze the process of ship berthing service reform Administrativedandokumen goods in the Port of Tanjung Perak Surabaya in order to achieve an increasein the volume of entry and exit of goods. To model ship berthing services and documentitems in the Administrative Port of Tanjung Perak Surabaya. The survey results revealedthat the reform process ship berthing services and goods at administrative documents Portof Tanjung Perak Surabaya, can be done by way of one-stop services (one stop services),supported by facilities and infrastructure to support the smooth running of the service.Model ship berthing services and goods at administrative documents Port of Tanjung Perakbased on the ten principles of service based on the minister's decision No. 63 of 2004related on the principle of service. Suggestion this research is the need for integration thatinvolves the participation of government, administrative Port of Tanjung Perak Surabaya,and the administrative services of the Port of Tanjung Perak Surabaya in order to reformthe service can run well and using a model of one-stop service so that the service can beintegrated quickly.Keywords: Service Reform, ship berthing, Documentation Handling Goods, Tanjung Perak,Surabaya